The Representation of Gender and Sexuality in Priya's Shakti (2012). Issue 1 (3rd April 2018) - Shrivastava, Nidhi
Abstract: As a response to the emerging discourse on violence against women in the aftermath of the heinous 2012 Delhi gang-rape case, filmmaker Ram Devineni and his collaborators Dan Goldman and Lina Shrivastava created Priya's Shakti – India's first augmented reality comic book geared towards young teenage children. This essay analyzes how the comic book represents Priya as a rape survivor. Using my interviews with Devineni and an analysis of the reception of Priya's Shakti, I argue that this work's success is a testament to the new forms of media that are being deployed across class and location, to create new conversations about taboo topics like female sexuality and rape. These new graphic media narratives, I contend, redeploy the power of mythological characters that are inspired by the classic Amar Chitra Katha comics. By recasting these mythological characters, they invite readers to see all cultural norms about gender and sexuality as malleable rather than fixed; this opens up a new space for exploring how a rape culture may be challenged and changed.